Those empty eyes [large type] - Donlea, Charlie (Thorndike Press large print mystery, 2023)
"Alex Armstrong has changed everything about herself--her name, her appearance, her backstory. She's no longer the terrified teenager a rapt audience saw on television, emerging in handcuffs from the quiet suburban home the night her family was massacred. That girl, Alexandra Quinlan, nicknamed Empty Eyes by the media, was accused of the killings, fought to clear her name, and later took the stand during her highly publicized defamation lawsuit that captured the attention of the nation. It's been ten years since, and Alex hasn't stopped searching for answers about the night her family was killed, even as she continues to hide her real identity from true crime fanatics and grasping reporters still desperate to locate her. As a legal investigator, she works tirelessly to secure justice for others, too. People like Matthew Claymore, who's under suspicion in the disappearance of his girlfriend, a student journalist named Laura McAllister. Laura was about to break a major story about rape and cover-ups on her college campus. Alex believes Matthew is innocent, and unearths stunning revelations about the university's faculty, fraternity members, and powerful parents willing to do anything to protect their children. Most shocking of all-as Alex digs into Laura's disappearance, she realizes there are unexpected connections to the murder of her own family. For as different as the crimes may seem, they each hinge on one sinister truth--no one is quite who they seem to be . "--